PENGARUH RETURN ON ASSETS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA BANK PEMERINTAH DAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rosyida, Ade Septia; Farina, Khoirina (Universitas Trilogi, 2023)
This research aims to examine the effect of Return On Assets (ROA), Leiveriage, and Company Size on Tax Avoiidance. This study uses a sample of banking companies, namely: Government and Conventional Banks listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. With the sample used in this research consisting of 20 banks. The analysis methods used are 1. Descriptive Statistical Analysis, 2. Panel Data Regression, 3. Classical Assumption Test, 3. Hypothesis Testing. The hypothesis tests used are: Multiple Linear Regression Test, Determination Coefficient Test, Simultaneous Significance Test (F Statistical Test), Individual Parameter Significance Test (t Statistical Test). The results showed that partially only Return On Assets (ROA) has a negative and significant effect on Tax Avoidance which is proxied by ETR. While Leverage and Company Size have no effect on Tax Avoidance. The results of the F test show that Return On Assets (ROA), Leverage, and Company Size together have an effect on Tax Avoidance.Keywords: ETR; Tax Avoidance; Return On Assets (ROA); Leverage; Company Size.